(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores key aspects of ensuring women’s social activity in Uzbekistan. It examines the state’s gender-focused policies, the role of social and economic conditions, and the challenges that limit women’s full participation in public, political, and economic life.